Management of acute ischemic stroke in the emergency department: optimizing the brain - Latha Ganti (International Journal of Emergency Medicine)
Abstract Acute ischemic stroke is a devastating condition that afflicts more than 12 million people every year. Globally, stroke is the 2nd leading cause of death and 3rd leading cause of disability worldwide. While not all patients can avail themselves of existing acute therapies, all patients can benefit from brain optimization measures. This paper details the 12 steps in the management of acute ischemic stroke in the emergency department.